Next-generation sequencing for the diagnosis of hepatitis B: current status and future prospects. (3rd April 2021) - Garcia-Garcia, Selene; Cortese, Maria Francesca; Rodríguez-Algarra, Francisco; Tabernero, David; Rando-Segura, Ariadna; Quer, Josep; Buti, Maria; Rodríguez-Frías, Francisco
ABSTRACT: Introduction: Hepatitis B virus (HBV) causes a complex and persistent infection with a major impact on patients health. Viral-genome sequencing can provide valuable information for characterizing virus genotype, infection dynamics and drug and vaccine resistance. Areas covered: This article reviews the current literature to describe the next-generation sequencing progress that facilitated a more comprehensive study of HBV quasispecies in diagnosis and clinical monitoring. Expert opinion: HBV variability plays a key role in liver disease progression and treatment efficacy. Second-generation sequencing improved the sensitivity for detecting and quantifying mutations, mixed genotypes and viral recombination. Third-generation sequencing enables the analysis of the entire HBV genome, although the high error rate limits its use in clinical practice.